2014
DOI: 10.2176/nmc.oa.2014-0129
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Bacterial Flora in the Nasal Cavity and the Sphenoid Sinus Mucosa in Patients Operated on with an Endoscopic Endonasal Transsphenoidal Approach

Abstract: The aim of this study was to analyze the bacterial flora in the nasal cavity and sphenoid sinus and evaluate the sensitivity of these bacteria to antibiotics that can be used to prevent postoperative meningitis. Bacteria of the preoperative nasal cavity and intraoperative sphenoid sinus mucosa were cultured and analyzed in 40 patients (20 men and 20 women; mean age, 52.2 years) who underwent endoscopic transsphenoidal surgery. The sensitivity of these bacteria to cephalosporin, a representative prophylactic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 14 publications
(15 reference statements)
1
17
0
Order By: Relevance
“…Investigations of the sinonasal tract have shown members of the corynebacteria, staphylococci and propionibacteria to be well represented in health [ 5 7 ]. In the present study, clonal libraries generated from the sinuses of NFPA patients were generally representative of such findings with either Staphylococcus epidermidis or Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations of the sinonasal tract have shown members of the corynebacteria, staphylococci and propionibacteria to be well represented in health [ 5 7 ]. In the present study, clonal libraries generated from the sinuses of NFPA patients were generally representative of such findings with either Staphylococcus epidermidis or Corynebacterium spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent survey of the nares (n = 1878) reported E. coli and Enterobacter aerogenes are carried by less than 6.1 and 2.6% of healthy adults, respectively [ 8 ]. With regards the sinuses, microbiota studies are generally more limited in terms of sample size, but typically report recovery of these bacterial taxa in less than 5% healthy individuals [ 7 , 9 ]. Rather, these bacteria are typically associated with infradiaphragmatic sources and have been implicated as potential pathogens in rhinosinusitis following their isolation in symptomatic individuals [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of hypothalamus-pituitary dysfunction is reported to be 4.2/100,000 per year, without sex differences; the prevalence is 45.5 per 100,000 people [18]. The rate of PCNSIs in patients with sellar region tumors ranges from 0.5-14% [19]. Some studies have shown the relationship between abnormal immune function and hypothalamus-pituitary dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%
“…She subsequently died of multifactorial causes. She is excluded from this analysis as (1) her CSF infection appears to be a complication of prolonged external ventricular drain use and (2) occurred 43 days after transsphenoidal surgery.…”
Section: Group A-limited Transsphenoidalmentioning
confidence: 99%